1985
DOI: 10.1159/000242141
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Responses to Growth Hormone Releasing Factor in Neonates

Abstract: The response of growth hormone (GH) to synthetic human growth hormone releasing factor (hGRF) administered intravenously was examined in 32 neonates aged 3–28 days. GH peaked at 30 min after hGRF administration and the mean ± SEM level of GH at maximal response was 66.4 ± 6.2 ng/ml. In the comparison between the neonates less than 7 days old and those more than 8 days old, between the neonates less than 37 weeks and those more than 38 weeks in gestational age, between the neonates under 2,500 g and those over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, Shimano et al (1985) observed no difference when comparing response to GRF in babies less than 7 days old to that in neonates older than 8 days. In our experimental conditions, the increase in plasma GH concentration following the same dose (50 pmoles.kg-!…”
Section: Introductionmentioning
confidence: 77%
“…However, Shimano et al (1985) observed no difference when comparing response to GRF in babies less than 7 days old to that in neonates older than 8 days. In our experimental conditions, the increase in plasma GH concentration following the same dose (50 pmoles.kg-!…”
Section: Introductionmentioning
confidence: 77%
“…At term [4], pituitary GH secretion is still enhanced compared with childhood, but there is a rapid decline of serum concentrations within the first postnatal days. Regulation by somatostatin and GH-releasing factor [5]is intact in term newborns. As the infant matures, there is a decrease in GH pulse frequency, pulse amplitude and nadir GH levels [4], resulting in a decrease of mean serum GH concentrations postnatally.…”
Section: Growth Hormonementioning
confidence: 99%
“…Rhe sus monkeys have also shown a greater GH response to GHRH in the immediate new born period, with a striking decrease in GH response after 48 h of age [27], Furthermore, using similar restraint and sampling meth ods to those used in the current study, we have previously shown that the serum GH response to exogenous GHRH administra tion decreased with advancing age from 1 to 28 days in a group of rhesus monkeys stud ied longitudinally [28]. There was no correla tion between GH and cortisol concentra tions and no consistent change in cortisol with age [28], GHRH administration to hu man neonates produced no difference in GH response in 3-to 7-day-old infants compared to infants aged 6-28 days in one study [29], but GHRH produced a greater response in infants at 3 days of age than at 30 days of age in another study [30]. Thus, early neonatal evidence suggests that the spontaneous de cline in GH concentration observed during the first few days of life may reflect a de crease in pituitary response to GHRH stimu lation.…”
Section: Discussionmentioning
confidence: 82%